Dampak Corporate Governance, ROA Dan Leverage terhadap Penerapan Tax Avoidance - Ike Dilasari; Norman Duma Sitinjak; Dewi Kusumowati (University of Merdeka Malang, 2021)
Companies need to make efficiency so that the profits obtained can be optimal. tax is one of the objects of company efficiency. tax avoidance is a way for companies to safely minimize the tax burden. safe because it does not violate tax rules. corporate governance, roa and leverage are variables that can affect tax avoidance activities. this study examines the impact of corporate governance, roa and leverage on the implementation of tax avoidance. the method used is quantitative. the companies studied are companies registered as CGPI participants. the analysis technique uses multiple regression analysis. the test results show that the three independent variables affect the implementation of tax avoidance. changes in corporate governance activities, roa value and leverage can result in changes in tax avoidance activities carried out by the company. CGPI participating companies need to focus more on corporate governance, roa and leverage in carrying out tax avoidance activities.